EBV-negative lymphoepithelial-like carcinoma of the lower lip - Almeida, Luciana Yamamoto; Silveira, Heitor Albergoni; Silva, Evânio Vilela; Barbeiro, Camila de Oliveira; Paula, Joaquim Augusto de; Bufalino, Andreia; Ribeiro-Silva, Alfredo; León, Jorge Esquiche (Autopsy and Case Reports, 2020)
Lymphoepithelial-like carcinoma (LEC) is a rare malignant neoplasm, which can be associated with Epstein-Barr virus (EBV) infection. Histologically, LEC is an undifferentiated carcinoma with an intermixed reactive lymphoplasmacytic infiltrate. LEC appears to be an uncommon tumor type of lip carcinoma. An 82-year-old white woman presented a lesion on her lower lip that developed over the last year. The lesion was characterized by ulceration with flat edges, hardened base, painful, and absence of regional lymphadenopathy. Microscopical analysis evidenced an intense inflammatory infiltrate, composed of lymphoplasmacytic cells, associated with scarce pleomorphic epithelial cells. Immunohistochemistry highlighted the LEC cells with strong expression of pan-CK AE1/AE3, EMA, p63, and p53. CD138 was also faintly positive. Ki-67 was >85%. In situ hybridization analysis did not show evidence of EBV. A diagnostic of EBV-negative LEC was made. We present an uncommon type of lip carcinoma, which can represent a diagnostic challenge for clinicians and pathologists.